Use of agricultural by-products in extruded gluten-free breakfast cereals - Santos, Priscila Alonso dos; Caliari, Marcio; Soares Junior, Manoel Soares; Silva, Kamilla Soares [UNESP]; Viana, Leticia Fleury; Caixeta Garcia, Lismaira Goncalves; Lima, Maria Siqueira de (Elsevier B.V., 2019)
The objective of this study was to evaluate the effect of the extrusion moisture and temperature on the physical characteristics of breakfast cereals. The chemical composition, microbiological risk and acceptance of the selected breakfast cereal with the best physical quality were assessed to determine the technological viability of the use of these by-products by the food industry. The response surface method and a rotatable central composite design were used, and a desirability test was performed based on adjusted regression models. The breakfast cereal produced under these conditions had protein, lipid and dietary fiber contents of 7.55, 0.97 and 6.12 g 100 g(-1), respectively. In regards to the sensory analysis, the evaluated breakfast cereal received average acceptance scores ranging from neither like or dislike to like moderately. The use of rice, passion fruit and milk by-products was shown to be an alternative for the production of extruded breakfast cereal.
Keywords: By-products; Extrusion; Sensory analysis; Centesimal composition; Microbiology